2015
DOI: 10.1111/tpj.13021
|View full text |Cite
|
Sign up to set email alerts
|

AmicroRNAallele that emerged prior to apple domestication may underlie fruit size evolution

Abstract: SUMMARYThe molecular genetic mechanisms underlying fruit size remain poorly understood in perennial crops, despite size being an important agronomic trait. Here we show that the expression level of a microRNA gene (miRNA172) influences fruit size in apple. A transposon insertional allele of miRNA172 showing reduced expression associates with large fruit in an apple breeding population, whereas over-expression of miRNA172 in transgenic apple significantly reduces fruit size. The transposon insertional allele wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 56 publications
(90 reference statements)
2
106
0
Order By: Relevance
“…Studies comparing cultivated rice with wild rice ( Oryza rufipogon ) found positively selected miRNAs and target genes in cultivated rice, suggesting that miRNAs were involved in or even drove rice domestication [39,40]. Another study suggested that a loss-of-function mutation in MIR172p improved fruit size during apple domestication [41]. …”
Section: Functional Divergence Of Mirnasmentioning
confidence: 99%
“…Studies comparing cultivated rice with wild rice ( Oryza rufipogon ) found positively selected miRNAs and target genes in cultivated rice, suggesting that miRNAs were involved in or even drove rice domestication [39,40]. Another study suggested that a loss-of-function mutation in MIR172p improved fruit size during apple domestication [41]. …”
Section: Functional Divergence Of Mirnasmentioning
confidence: 99%
“…Plant species have multiple MIR172 genes that can produce conserved mature miR172 sequences in different tissues and at different developmental stages. [1][2][3] The mature miR172 sequences target mRNA of a subfamily of APETALA2 (AP2) genes by sequence complementation and repress expression by inhibiting translation or initiating degradation of the target mRNA. [4][5][6][7] As members of the AP2 subfamily have different temporal and spatial expression patterns 3,8,9 and interact with different proteins, 10 the MIR172 gene family potentionally can affect many aspects of plant development.…”
mentioning
confidence: 99%
“…Because of this central role in the regulation of development, it was proposed that miRNAs might be good targets for the development of tools to improve crop productivity (Yao et al, 2015;Tang and Chu, 2017;Xu et al, 2018). In plants, miRNA-encoding genes are transcribed as primary transcripts harboring a fold back structure that is processed by DICER-LIKE 1 (DCL1).…”
Section: Introductionmentioning
confidence: 99%